Development of a growth-coupled selection platform for directed evolution of heme biosynthetic enzymes in Corynebacterium glutamicum - Zhou, Yingyu; Chen, Jiuzhou; Pu, Wei; Cai, Ningyun; Che, Bin; Yang, Jinxing; Wang, Mengmeng; Zhong, Shasha; Zuo, Xingtao; Wang, Depei; Wang, Yu; Zheng, Ping; et al. (Frontiers in Bioengineering and Biotechnology, 2023)
Heme is an important tetrapyrrole compound, and has been widely applied in food and medicine industries. Although microbial production of heme has been developed with metabolic engineering strategies during the past twenty years, the production levels are relatively low due to the multistep enzymatic processes and complicated regulatory mechanisms of microbes. Previous studies mainly adopted the strategies of strengthening precursor supply and product transportation to engineer microbes for improving heme biosynthesis. Few studies focused on the engineering and screening of efficient enzymes involved in heme biosynthesis. Herein, a growth-coupled, high-throughput selection platform based on the detoxification of Zinc-protoporphyrin IX (an analogue of heme) was developed and applied to directed evolution of coproporphyrin ferrochelatase, catalyzing the insertion of metal ions into porphyrin ring to generate heme or other tetrapyrrole compounds. A mutant with 3.03-fold increase in kcat/KM was selected. Finally, growth-coupled directed evolution of another three key enzymes involved in heme biosynthesis was tested by using this selection platform. The growthcoupled selection platform developed here can be a simple and effective strategy for directed evolution of the enzymes involved in the biosynthesis of heme or other tetrapyrrole compounds.